Financial Influences Impacting Young Adults’ Relationship Satisfaction: Personal Management Quality, Perceived Partner Behavior, and Perceived Financial Mutuality - Dung Minh Mao; Sharon M. Danes; Joyce Serido; Soyeon Shim (Journal of Financial Therapy, 2017)
In this study, we investigated the extent to which young adults’ (n=274) personal financial management quality and perceived partners’ financial behavior were associated – both directly and indirectly via perceived financial mutuality – with relationship satisfaction in committed relationships. The study was grounded in Social Exchange Theory (SET). A path analysis revealed that perceived partner’s financial behavior had a direct association with perceived financial mutuality, which, in turn, had a direct association with relationship satisfaction. In contrast, the participant’s financial management quality and relationship satisfaction were not directly associated nor was they indirectly associated through perceived financial mutuality. Perceived financial mutuality had the largest effect on relationship satisfaction. These findings indicate that perceived financial mutuality plays a key role both directly and as a mediator on relationship satisfaction for these young adults. The implications of the findings provide insights for designing preventive financial strategies early in romantic relationships.
Keywords: finances and relationships; financial management; financial behavior; financial values; relationship satisfaction; young adults